Clinical aspects of TP53 gene inactivation in diffuse large B-cell lymphoma - Elena N. Voropaeva; Tatyana I. Pospelova; Mikhail I. Voevoda; Vladimir N. Maksimov; Yuriy L. Orlov; Olga B. Seregina (BMC, 2019)
Abstract Background The knowledge about specific mechanisms generating TP53 dysfunction in diffuse large B-cell lymphoma is limited. The aim of the current study was to comprehensively explore TP53 gene variability resulting from somatic mutations, promoter methylation, and allelic imbalance in tumorous tissue of diffuse large B-cell lymphoma (DLBCL). Methods DNA samples from 74 patients with DLBCL were used. Genomic DNA was isolated from paraffin blocks of lymph nodes or from extranodal biopsies of tumors by the phenol-chloroform extraction method with guanidine. Analysis of coding sequences of the TP53 gene was based on Sanger's direct sequencing method. The methylation status of the TP53 promoter was analyzed using by methylation-specific PCR on bisulfite-converted DNA. Assessment of the detected mutations was carried out in the IARC TP53 Database and the TP53 UMD mutation database of human cancer. Results The mutations in regions coding for the DNA-binding domain were prevalent (95%). In the analyzed sample of patients, codons 275, 155, 272, and 212 were hotspots of mutations in the TP53 gene. In addition, functionally significant intron mutations (IVS6-36G > C and IVS5 + 43G > T) were detected. Instances of TP53 promoter methylation were observed only in a few samples of diffuse large B-cell lymphoma tissue. Furthermore, loss of heterozygosity was revealed only in the subgroup of patients with altered status of the gene (mutations were detected in five patients and promoter methylation in one case). Conclusions Thus, the results suggest that there are two sequential events in the formation of diffuse large B-cell lymphoma in at least some cases. The first event is mutation or methylation of the TP53 promoter, leading to appearance of a cell with increased risk of malignant transformation. The second event is the loss of an intact allele of the gene; this change is necessary for tumorigenesis. We identified TP53 mutation patterns in a Russian cohort of patients with de novo DLBCL who were treated with R-CHOP and R-CHOP-like regimens and confirmed that TP53 mutation status is a valuable prognostic biomarker.